(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2021)
Traditional healers have long regarded ethnomedicine as a fascinating and appealing topic of study. This makes the proper identification of these plant species all the more vital. It’s also worth noting that female butterflies are endowed with the capacity to recognise plants that are conducive to oviposition and, in turn, provide nourishment for their larvae. It is possible that butterflies’ ability to choose the correct plant at the right moment demonstrates the relevance of plant secondary metabolites. This class of metabolites is also the foundation for a number of pharmaceutical compositions. As a result, this research aims to emphasise the folklore therapists’ use of plant species in the tribal areas of West and East Midnapore, West Bengal, India. The identification of butterflies that feed their larvae on the same plant species was also completed.